A trianoni diktátum aláírója : a miniszter Benárd Ágoston - Vizi, László Tamás (Közép-Európai Közlemények, 2010)
In the commission of the Hungarian Government, Ágoston Benárd, welfare and labour minister, Alfréd Drasche-Lázár extraordinary delegate and plenipotentiary minister signed the Trianon peacetreaty, what divided the historical Hungary in 4th June 1920. and disannexed the two-third of the country and more million Hungarians. The historical literature, both the written and the electronic press consider them, as unimportant politicians, who departed from the political life just after the signature, and strengthen the idea that this two people were chosen randomly, maybe chosen with lot. Weightless the fact of the signature with this. The undermentioned study would like to deny this old myth, with presenting Ágoston Benárd’s Christian Socialist political representative and ministerial job, which he made in the interest of the solution of the social crisis after the wartime defeat and the revolutions. Emphasizing, that he remained an active character of the Hungarian political and public life, after the signature of the Trianon diktat too.